2015
DOI: 10.1016/j.supflu.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional groups on the solubilities of polyhedral oligomeric silsesquioxanes (POSS) in supercritical carbon dioxide

Abstract: , 88 pages In this study, the phase behavior of the binary systems containing CO2 and various hybrid polyhedral oligomeric silsesquioxanes (POSS) with different functional groups were investigated. A high-pressure view cell was used to measure the dewpoints or cloud-points at temperatures between 308K and 323K, up to 30 MPa. Among the studied POSS structures, methacryl, isooctyl and octaisobutyl POSS were observed to form homogenous solutions with CO2, while octamethyl POSS was found to be insoluble in the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 94 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…In the present work, however, the relatively higher T g and the polar SO 2 groups of PES are likely causes of the favorable interaction with the scCO 2 and shH 2 O at higher soaking temperatures. Others have also reported of effect of higher solubility in scCO 2 at higher temperatures due to favorable interactions with certain functional groups . Therefore, we postulate that increasing the temperature leads to high degree of swelling by the shH 2 O and scCO 2 .…”
Section: Resultsmentioning
confidence: 59%
“…In the present work, however, the relatively higher T g and the polar SO 2 groups of PES are likely causes of the favorable interaction with the scCO 2 and shH 2 O at higher soaking temperatures. Others have also reported of effect of higher solubility in scCO 2 at higher temperatures due to favorable interactions with certain functional groups . Therefore, we postulate that increasing the temperature leads to high degree of swelling by the shH 2 O and scCO 2 .…”
Section: Resultsmentioning
confidence: 59%
“…For this, the films were processed with two different types of additives. One of them was the TFPOSS, which was shown recently to be significantly scCO2-soluble [40], and the other was OMPOSS, which was found to be insoluble in the supercritical fluid [41]. The scCO2 processing of the films were performed at 20.7 MPa and 313 K for 2 hr, after which the films were vented at a rate of 10.3…”
Section: Resultsmentioning
confidence: 99%
“…In polymer processing with scCO2, such particles can act as heterogeneous nucleating agents, which stimulate higher rate of cell nucleation by decreasing the free energy barrier for nucleation and provide new sites for cell formation [5,38,39]. We used two types of POSS to observe their effects on the formation of pores in PLLA; a CO2-philic type, trifluoropropyl polyhedral oligomeric silsesquioxane (TFPOSS) [40], and a non CO2-philic type, octamethyl polyhedral oligomeric silsesquioxane (OMPOSS) [41]. Even though in literature it was reported that for PLLA with crystallinity greater than 30%, saturation temperatures close to the melting temperature of PLLA were required to obtain a porous structure with scCO2 processing [31,42], our results showed that up to 40% porosity could be obtained in the polymer matrix when a CO2-philic POSS was added into the PLLA with crystallinity greater than 30% and the composite was processed at the scCO2 saturation temperature and pressure of 313 K and 20 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, aggregation of POSS materials and the limitation of their solubility are important hindrances of the POSS applications . Recently it was shown that POSS can be CO 2 ‐philic and solubilized in supercritical CO 2 provided that it has certain functional groups, which allows applications of POSS in environmentally benign supercritical processing of materials …”
Section: Introductionmentioning
confidence: 99%
“…This, in return, can enhance the entropy of mixing, and thus the solubility of the compound in supercritical carbon dioxide (scCO 2 ) . In previous solubility studies, trifluoropropyl POSS was found to be highly soluble in scCO 2 , while octamethyl POSS was insoluble . In a recent study trifluoropropyl POSS was used as a pore inducer in supercritical foaming of poly( L ‐lactic acid) (P L LA) with crystallinity greater than 30% .…”
Section: Introductionmentioning
confidence: 99%